Answer :


P (X = 1) = P (X = 2) = α

P (X= 4)=?

P(x=r)= nCr pr qn-r

P(x=1)= nC1 p1 qn-1

=npqn-1 (1)

P(x=2)= nC2 p2 qn-2


Equating both equations ,we have:

2q = (n-1) p

4q2 = (n-1)2 p2

P(x=4)= nC4 p4 qn-4

For large n; n



Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses

A box has 100 penMathematics - Exemplar

State True or FalMathematics - Exemplar

A random variableMathematics - Board Papers

How many times muMathematics - Board Papers

A card from a pacMathematics - Board Papers

An experiment sucMathematics - Board Papers

A bag A contains Mathematics - Board Papers

On a multiple choMathematics - Board Papers

Mark the correct RD Sharma - Volume 2